Combined use of waist and hip circumference to identify abdominally obese HIV-infected patients at increased health risk. - Trevor O'Neill (Public Library of Science (PLoS), 2013)
Objectives To determine whether for a given waist circumference (WC), a larger hip circumference (HC) was associated with a reduced risk of insulin resistance, type 2 diabetes (T2D), hypertension and cardiovascular disease (CVD) in HIV-infected patients. A second objective was to determine whether, for a given WC, the addition of HC improved upon estimates of abdominal adiposity, in particular visceral adipose tissue (VAT), compared to those obtained by WC alone. Methods HIV-infected men (N = 1481) and women (N = 841) were recruited between 2005 and 2009. WC and HC were obtained using standard techniques and abdominal adiposity was measured using computed tomography. Results After control for WC and covariates, HC was negatively associated with risk of insulin resistance (p<0.05) and T2D [Men: OR = 0.91 (95% CI: 0.86-0.96); Women: OR = 0.91 (95% CI: 0.84-0.98)]. For a given WC, HC was also negatively associated with a lower risk of hypertension (p<0.05) and CVD [OR = 0.94 (95% CI: 0.88-0.99)] in men, but not women. Although HC was negatively associated with VAT in men and women after control for WC (p<0.05), the addition of HC did not substantially improve upon the prediction of VAT compared to WC alone. Conclusions The identification of HIV-infected individuals at increased health risk by WC alone is substantially improved by the addition of HC. Estimates of visceral adipose tissue by WC are not substantially improved by the addition of HC and thus variation in visceral adiposity may not be the conduit by which HC identifies increased health risk.